Variants c.677 C>T, c.1298 A>C in MTHFR, and c.66 A>G in MTRR Affect the Occurrence of Recurrent Pregnancy Loss in Chinese Women - Zhang, Yan (Genet Test Mol Biomarkers, 2020)
Objective: Although genetic variants of key enzymes in the folic acid-methionine metabolic circulation, including methylenetetrahydrofolate reductase (MTHFR) and methionine synthase reductase (MTRR) were thought to be related to the risk of recurrent pregnancy loss (RPL), the results of recent studies have been inconsistent. Therefore, the present retrospective case–control study was designed to explore whether the variants c.66A>G in MTRR and c.677C>T and c.1298A>C in MTHFR are associated with the susceptibility of RPL in Southeast Chinese women. Materials and Methods: In total, samples from 237 RPL patients and 618 healthy controls were collected and genotyped by fluorescent quantitative polymerase chain reaction. The frequencies of the variants were calculated and compared between the two groups. The relative risk of the various genotypes was further determined by calculating the odds ratio (OR) at a 95% confidence interval (CI). Results: A significant positive correlation was observed between the variants MTHFR c.677C>T, MTHFR c.1298A>C, MTRR c.66A>G, and RPL susceptibility (MTHFR c.677C>T, OR = 0.74, 95% CI = 0.58–0.95, p = 0.02; MTHFR c.1298A>C, OR = 1.39, 95% CI = 1.09–1.77, p = 0.008; MTRR c.66A>G, OR = 1.38, 95% CI = 1.10–1.73, p = 0.006). Further analysis of the genotypic distributions of the three variants between the two groups showed that the MTHFR c.677C>T heterozygote was associated with lower RPL risk, while the MTHFR c.1298A>C variant and MTRR c.66A>G heterozygote were correlated with higher RPL risk (dominant model, MTHFR c.677C>T, OR = 0.70, 95% CI = 0.52–0.95, p = 0.02; MTHFR c.1298A>C, OR = 1.39, 95% CI = 1.03–1.88, p = 0.032; MTRR c.66A>G, OR = 1.62, 95% CI = 1.20–2.19, p = 0.002). Conclusion: MTHFR c.677C>T and c.1298A>C and MTRR c.66A>G were associated with RPL in Southeast Chinese women.